Emotional and behavioral problems in childhood: An instrument for early identification and prevention (Journal of Parents and Teachers, 2013)
The article discusses the importance of problems early detection and describes a new psychological assessment instrument to measure emotional and behavioral problems in childhood. The main purpose of the work was to create a screening test for children's behavior problems (SPECI) and to carry out psychometric analyses of its reliability and validity. The sample comprised 1,272 participants, 671 boys and 601 girls, ages between 5 and 12 years, of whom 937 randomly selected individuals had no clinical diagnosis, and 335 intentionally selected individuals had a clinical diagnosis (criterial groups). A descriptive, correlational and cross-sectional design was used. The results obtained reveal that the SPECI: 1) has high internal consistency; 2) it allows discrimination of children with and without behavior problems; children with and without emotional problems; and children with and without intellectual problems, which confirms its criterial validity; 3) no differences were found between boys and girls in withdrawal problems and somatization; however, higher scores were confirmed in boys in the remaining diagnostic categories (anxiety, dependent children, thought problems, attention-hyperactivity, disruptive behavior, academic performance, depression, and violent behavior). Factor analysis revealed two factors, internalizing and externalizing behavior problems.
Keywords: behavior problems; emotional problems; behavior inventories; childhood; School guidance